Modeling of a Business Incubator Program for Islamic Youth Organizations for the Development of Superior Rural Products - Mawi Khusni Albar; Khairunnisa Dwinalida; Yuliana Yuliana (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
By raising research questions about What is an effective business incubator strategy in developing superior products in rural areas? and How effective is the Business Incubator Program Modeling for Islamic Youth Organizations for Developing Superior Rural Products in Cilacap Regency, this study focuses on looking at the effectiveness of business incubators as well as the role of Islamic youth organizations in cultivating village potential so that they are able to drive the economy of their region. A qualitative descriptive approach carried out for 3 months was chosen as a technique for obtaining data. Research was conducted in sub-districts/villages that have superior products that can be developed through business incubators implemented by Islamic youth organizations in the village under the guidance of the village/sub-district. Furthermore, in determining informants a purposive sampling technique was used. Primary data (Interviews and Observations) and secondary data (Documentation and Literature) were extracted from research subjects to answer research questions. Furthermore, to describe the findings of this research, Donald Van Metter and Carl Van Horn's model is used with six variables that influence policy performance to analyze the effectiveness of OKp. Field findings provide an illustration that in simple terms, business incubation that can be carried out by Islamic Youth Organizations is a community empowerment strategy. This strategy is considered effective, especially since youth organizations have strength, namely a mass base, as well as organizational skills. The business incubation model with a rural community empowerment strategy leads to the classic model, namely joint discussions, joint deliberations. This model is effective, besides being easy and affordable.